IMPLEMENTASI AKUNTANSI KOMBINASI BISNIS SEBELUM DAN SETELAH ADOPSI IFRS PADA PERUSAHAAN SEKTOR KONSUMSI DI INDONESIA - Naila Mafazati Ulya; Amrie Firmansyah (Universitas Muhammadiyah Jember, 2021)
This study aims to analyze the implementation of business combination accounting before and after the IFRS adoption in Indonesia. This study uses a qualitative method with a content analysis approach. The data used in this study is secondary data, the financial statements of consumption sector companies listed on the Indonesia Stock Exchange from 2009 to 2019 and obtained from www.idx.co.id and www.idnfinancials.com. Using purposive sampling, the sample used in the analysis of this study amounted to 6 companies for 11 years (66 observations). This study concludes that before the IFRS adoption was implemented in Indonesia, some companies implemented the pooling of interest accounting methods for their business combinations. In contrast, other companies used the purchase method, and some companies did not disclose the accounting recording method of their business combination. Besides, several companies do not recognize goodwill, while other companies have recognized and harmonized goodwill under applicable standards. At the beginning of adopting IFRS in Indonesia, all companies that had goodwill had stopped amortizing goodwill and tested the impairment every year. However, some companies still did not fully implement business combination accounting under financial accounting standards. Starting in 2015, all companies have improved their accounting for business combinations, especially in the presentation and measurement of transactions, to be more detailed and following applicable standards.